Percutaneous flexor digitorum brevis tenotomy: An anatomical study. Issue 2 (February 2022) - Carvalho, Paulo; Dalmau-Pastor, Miki; Lozi, Caroline; Souza, Matheus; Lucas-Y-Hernandez, Julien; Laffenêtre, Olivier
Highlights: First anatomical study about the percutaneous FDB tenotomy. Percutaneous FDB tenotomy proved to be safe, respecting FDL and plantar digital nerves. Percutaneous FDB tenotomy is effective regarding PIP arthrolysis but a technical improvement is required to achieve a reliable section of both FDB slips. Plantar proximal interphalangeal arthrolysis could be the single most critical element for claw toe correction. Summary: Introduction: A percutaneous selective flexor digitorum brevis (FDB) tenotomy and a proximal interphalangeal (PIP) joint arthrolysis may correct a lesser claw toe deformity keeping flexor digitorum longus (FDL) and active flexion. Our study aimed to verify if the procedure was effective and reliable and if it respects the surrounding soft tissues. Material and method: Twelve cadaveric lateral toes were used. A dissection ensured the integrity of both digital nerves, FDL and flexor pulleys and assessed the section of both FDB slips and PIP arthrolysis. Results: A complete section of the two FDB slips was observed in 4 cases (33%). Arthrolysis was achieved in all cases. Surrounding soft tissues were found intact in all cases. Conclusion: This procedure is effective regarding PIP arthrolysis, but a technical improvement is required to achieve a reliable section of both FDB slips. In the hands of an experienced surgeon, it has proven to be safe.